Efectos en los parámetros productivos de la adición del deshidratado de plectranthus amboinicus en el balanceado de cerdos de ceba - Vega Tinoco, Mayte Madelaine (2018)
Resistance to antibiotics is shown as a real threat to the fight against several diseases, that is, partly due to the use and abuse of these drugs, which triggers a tolerance of the microbes to them, this being the most important cause but not only the only reason why the administration of drugs for the prevention and management in the companies of chemical products of animal protein is the abuse of these chemicals causes the problem of bacterial resistance that puts human health at risk, since "Resistance bacteria transfer their defense mechanisms and resistance to other microorganisms from the environment and man. This investigation was realized in "Los Hermanos" farm. That farm is localized in Balao/Guayas Province. Its owner is Mr. David Machuca Granda. This jobs was made to quantify and evaluate the productive parameters. Also it has the microbiological analysis with (Plectranthus amboinicus) dehydrated and ground balanced feed. That process (Plectranthus amboinicus) began to plant in a little places at the "Universidad Técnica de Machala".We took care with the plantation and the with the harvest. The land plots were too small we had to collect oregano in Piñas and Santa Rosa rural zones to complete the project. Our results were 80 porks with 49 days born. It was possible because we had worked in 56 days’ full time. We worked according to the techniques and rules of the (SUPERMAG) interprice. Those 20 porks were distributed in 4 gropus without repeat. The witness (el testigo) treatment 1. Treatment 2 (P. amboinicus 0.25%). Treatment 3 (P. amboinicus 0.50%). Treatment 4 (P. amboinicus 0, 75%). In this investigation was used balanced feed without antibiotics or any drogs. It was talked to Dr. Reinaldo Villacreses of Wayne enterprize, we had Santa Rosa as a distribution place. The activities were: Take the consume registers every day, take the porks weight at week and take stool test (it was done at the beginning, the middle and the final of the process. The variables to investigate were: The liveweight animals (kg), food to consume (kg) and the food conversion, mortality colimetria analysis and total flora. About the food conversion we can say didn’t have significative values between 4 groups. The result obtained in our investigation demostate tha the differences about productive parameters were not sigificative. The colimetria and total flora had featured results in the 4th group. We can confirm, in our investigation didn´t exist mortality cases. Since the beginning and final.